Study guides

Q: How do you solve x-3 plus 7 equals 2?

Write your answer...

Submit

Related questions

-2 plus 5 equals +3

Suppose x3-4x = 0. To solve, factor: x3-4x = x(x2-4) = x(x+2)(x-2) = 0 Now, a product equals 0 if and only one or more of the factors equals 0, so set each factor to 0 and solve. The roots are 0,-2 and +2.

(xn+2-1)/(x2-1)

(x - 1)(x^2 - 5x + 2)

3 + 2 + 25*3 - 6 = 3 + 2 + 75 - 6 = 74

x3+3x2+3x+2 divided by x+2 equals x2+x+1

-2+5=3

x3 + x2 - x = 0 ∴ x2 + x - 1 = 0 ∴ x2 + x + 0.25 = 1.25 ∴ (x + 0.5)2 = 1.25 ∴ x + 0.5 = ± 1.251/2 ∴ x = -0.5 ± 1.251/2

Y equals 1 and X equals 1

(a) y = -3x + 1

3

3

3

n= -2

The answer is x = 2.

Ln 4 + 3Ln x = 5Ln 2 Ln 4 + Ln x3= Ln 25 = Ln 32 Ln x3= Ln 32 - Ln 4 = Ln (32/4) = Ln 8= Ln 2

Yes.

x = 5, y = -1

c= -2 2/7 OR -2.285714

x3 + 8 = 0, then x3 = -8, therefore x = -2 -2 x -2 = 4 4 x -2 = -8

You can't solve it. But you can simplify it to get: 4x+y=2

3

20

7x + 2 = 5,6

(2,-2)